Surface water resources assessment of the Tonle Sap and Mekong Delta River Basin Groups improving climate resilience, productivity, and sustainability. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
The Tonle Sap and Mekong Delta RBGs are crucial to the ecosystem and economy of Cambodia, especially in agriculture and fisheries. But the RBGs are susceptible to floods, typhoons, and droughts that can have a damaging impact on infrastructure and crops. The brief recommends integrating climate adaptation measures with investments and development and management plans for climate resilience and the sustainable use of water resources in the RBGs.
Keywords: Agriculture -- Economic aspects -- Cambodia; Natural resources -- Cambodia; Electronic book